(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Abrus precatorius Linn. (Fabaceae) pericarps are used for the treatment of sciatica and alopecia which comprises the toxic protein and alkaloids, abrine, trigonelline, choline, and hypaphorine. Ayurveda urges the use of Abrus pericarps after the Shodhana process (detoxification). The current study was aimed at performing the Shodhana process, Swedana (boiling) of A. precatorius pericarps using cow’s milk, and Kanji (sour gruel) as a medium and to evaluate the acute toxicity of pericarps before and after detoxification in cow’s milk and Kanji. Materials and Methods: The acute toxicity study was carried out as per organization for economic cooperation and development guidelines 425. In acute toxicity study, the intraperitoneal dose (0.5, 1, and 2 mg/kg) of Ashodhita (unprocessed) and Shodhita (processed) white and black varieties of pericarps of A. precatorius was administered to 30 groups in a single dose, and general behavior, adverse effects, and mortality were determined up to 72 h. Results and Discussion: In acute toxicity, Ashodhita white and black varieties of pericarps of A. precatorius were found toxic, whereas neither mortality nor any significant alteration in behavior was observed in black varieties of pericarps of Shodhita A. precatorius, while some mortality and alteration in behavior were observed in white varieties of pericarps of Shodhita A. precatorius. Conclusion: The white varieties of pericarps are more toxic than black varieties of A. precatorius. It was also found that Shodhana in Kanji is more effective than cow’s milk.